Investigation on heat conduction of multi-sized sintered-ceramic powders based on Monte-Carlo method. (February 2023) - Zhang, Yuankun; Wu, Qizheng; Han, Zhuosheng; Rhamdhani, Akbar; Guo, Chunsheng; Brooks, Geoffrey
Highlights: An analytic model for ETC of sintered multi-sized oxide particles. The model is based on the Monte-Carlo method and neck formation theory. A special designed vacuum ETC measurement was fabricated. Model was experimentally validated by the measured data. The sensitivity of ETC to multiple factors was explored based on the new model. Abstract: Thermophysical property prediction of sintered lunar regolith plays a crucial role in developing extraterrestrial thermal processing techniques for In-situ Resource Utilization (ISRU) on the lunar surface since the Moon has been regarded as an outpost of deep space exploration. It is widely established that well-designed thermal processing can improve the mechanical and thermal properties of powdered material for industrial applications. Varying particle sizes and compositions significantly impact the sintering neck formation and heat transfer between solid particles. Previous studies have developed several parametric expressions for thermal conductivity between sintered mono-sized metallic or oxide particles. However, only a few concentrated on evaluating the thermal conductivity of sintered bodies with multi-sized powders. In this study, an analytical model for predicting the Effective Thermal Conductivity (ETC) of sintered ceramic samples fabricated using bi-sized particles was developed. The sintering contact between grains was estimated by an algorithm that couples the Monte-Carlo method with the neck formation theory. Here, samples of two oxides, alumina and silica, with different granularity fractions were prepared to simulate the lunar regolith. Volume ratios of small (radius of 5 μm) to large (radius of 22.5 μm) were 4:1, 2:1, and 1:2, respectively. The presented model was validated by ETC data measured by a special-designed apparatus, as well as the specific surface area within porous samples through the BET technique. The simulated results agree well with the measured data of samples with a single chemical component (RMSE=8.1%). However, the predicted ETC values for the mixture of two oxides (50/50 Vol.%) were about twice the measured results. The formation of mullite, verified by X-Ray Diffraction (XRD) analysis, was probably the main reason for the overvalued modeling ETC. Furthermore, the presented model was applied to analyze the sensitivity of ETC to important factors of ceramic mixtures. The results showed that the curvature deficiency between multi-sized particles influences the neck growth rate of the sintering necks compared with the mono-sized scenario.